MANAJEMEN PENDIDIKAN KARAKTER DALAM IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DI SMP NEGERI 1 KERTEK KABUPATEN WONOSOBO - Dyah Nuraeni; Nurkolis; I Made Sudana (STKIP Subang, 2024)
Character is the main aspect in shaping a person's qualities to become a noble person. The focus of the research is to describe and analyze character education management in the implementation of the Strengthening Pancasila Student Profile Project at SMP Negeri 1 Kertek Wonosobo Regency. The research approach used is qualitative. This type of research is a case study. This research uses triangulation of sources and methods. Data analysis in three steps: data reduction, presenting data, and drawing conclusions. The research results show that: 1) planning is carried out using planning procedures including identification of needs, school programs, school program priorities, and school program socialization. 2) organizing is carried out using organizational procedures including placement of school resources, organizational development, assignment and delegation of authority. 3) the mobilization is carried out by the school principal including the principal's direction and the principal's motivation. 4) supervision carried out by the school principal includes making assessments, evaluating implementation activities, and following up.